Environmental cluster effects and galaxy evolution: The H i properties of the Abell clusters A85/A496/A2670. Issue 1 (8th September 2022) - López-Gutiérrez, M M; Bravo-Alfaro, H; van Gorkom, J H; Caretta, C A; Durret, F; Núñez-Beltrán, L M; Jaffé, Y L; Hirschmann, M; Pérez-Millán, D
ABSTRACT: We study the impact of the local environment on the transformation of spiral galaxies in three nearby ( z < 0.08) Abell clusters: A85/A496/A2670. These systems were observed in H i with the Very Large Array, covering a volume extending beyond the virial radius and detecting 10, 58, and 38 galaxies, respectively. High fractions (0.40–0.86) of bright spirals [log( M * /M⊙ ) = 9−10] are not detected in H i . We provide further evidence of environmental effects consisting in significant fractions (0.10–0.33) of abnormal objects and a number of red (passive) spirals, suggesting an ongoing process of quenching. Ram-pressure profiles and the sample of the brightest spirals used as test particles for environmental effects indicate that ram-pressure plays an important role in stripping and transforming late-types. Phase-space diagrams and our search for substructures helped to trace the dynamical stage of the three systems. This was used to compare the global cluster effects versus pre-processing, finding that the former is the dominating mechanism in the studied clusters. By contrasting the global distribution of H i normal versus H i disturbed spirals in the combined three clusters, we confirm the expected correlation of disturbed objects located, on average, at shorter projected radii. However, individual clusters do not necessarily follow this trend, and we show that A496 and A2670 present atypical behaviour. In general, we provide conclusive evidence about the dependence of the transformation of infalling spirals on the ensemble of cluster properties like mass, ICM density, dynamical stage, and surrounding large-scale structure.